The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ppul.1113
|View full text |Cite
|
Sign up to set email alerts
|

Lung function testing in infants with cystic fibrosis: Lessons from the past and future directions

Abstract: Despite the increasing awareness of the need to identify early pulmonary changes in cystic fibrosis (CF) noninvasively, the role of lung function testing in infancy and early childhood remains less clear than in older children with CF. The aim of this review is to summarize available data, discuss the information gained from these publications, and put this information into perspective with more recent developments of lung function testing in both infants and older children with CF. While some of the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 87 publications
2
29
1
2
Order By: Relevance
“…Relationship with previous studies of lung function in infants and young children with cystic fibrosis Despite the popularity of the tidal rapid thoracic compression technique, [36][37][38] recent studies have suggested that the raised volume technique is a more sensitive means of identifying diminished airway function in infants with cystic fibrosis. 11 12 There is now clear evidence that the MBW technique detects abnormal lung function more readily in both preschool and school age children with cystic fibrosis than spirometry, 1 13 15 but this does not seem to be the case during infancy.…”
Section: Strengths and Limitationsmentioning
confidence: 87%
“…Relationship with previous studies of lung function in infants and young children with cystic fibrosis Despite the popularity of the tidal rapid thoracic compression technique, [36][37][38] recent studies have suggested that the raised volume technique is a more sensitive means of identifying diminished airway function in infants with cystic fibrosis. 11 12 There is now clear evidence that the MBW technique detects abnormal lung function more readily in both preschool and school age children with cystic fibrosis than spirometry, 1 13 15 but this does not seem to be the case during infancy.…”
Section: Strengths and Limitationsmentioning
confidence: 87%
“…The utility of lung function studies to detect early abnormalities in infants with CF have been previously reviewed [59]. The RVRTC technique can identify diminished lung function in infants diagnosed both clinically [60] and by newborn screening [61].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…There have been a few intervention studies in CF that have used infant lung function as an outcome [59]. The RVRTC technique has been used in two safety studies of hypertonic saline to demonstrate acute tolerability [19,20,66,67].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…This study in minimally symptomatic infants suggested that the early structural airway changes led to bronchiectasis and that chronic infection might be a secondary contributor to airway remodeling. Newer, sensitive pulmonary function studies also reported diminished airway function in infants soon after diagnosis with CF (Gappa et al, 2001). Many of these infants had no history of prior clinical infection.…”
Section: Introductionmentioning
confidence: 99%